Sulfur polymerization strategy based on the intrinsic properties of polymers for advanced binder‐free and high‐sulfur‐content Li–S batteries. Issue 1 (16th January 2023) - Song, Zihui; Zhang, Tianpeng; Liu, Siyang; Shao, Wenlong; Jiang, Wanyuan; Mao, Runyue; Jian, Xigao; Hu, Fangyuan
Abstract: Lithium–sulfur (Li–S) batteries are the promising next‐generation secondary energy storage systems, because of their advantages of high energy density and environmental friendliness. Among numerous cathode materials, organosulfur polymer materials have received extensive attentions because of their controllable structure and uniform sulfur distribution. However, the sulfur content of most organosulfur polymer cathodes is limited (S content <60%) due to the addition of large amounts of conductive agents and binders, which adversely affects the energy density of Li–S batteries. Herein, a hyperbranched sulfur‐rich polymer based on modified polyethyleneimine (Ath‐PEI) named carbon nanotube‐entangled poly (allyl‐terminated hyperbranched ethyleneimine‐random‐sulfur) (CNT/Ath‐PEI@S) was prepared by sulfur polymerization and used as a Li–S battery cathode. The high intrinsic viscosity of Ath‐PEI provided considerable adhesion and avoided the addition of PVDF binder, thereby increasing the sulfur content of cathodes to 75%. Moreover, considering the uniform distribution of elemental sulfur by the polymer, the utilization of sulfur was successfully improved, thus improving the rate capability and discharge capacity of the battery. The binder‐free, sulfur‐rich polymer cathode exhibited ultra‐high initial discharge capacity (1520.7 mAh g −1 at 0.1 C), and high rate capability (804 mAh g −1 at 2.0 C). And cell‐level calculations show that the electrode exhibits an initial capacity of 942.3 mAh g −1 electrode, which is much higher than those of conventional sulfur‐polymer electrodes reported in the literature. Abstract : A novel polymer framework that shows intrinsic viscosity and abundant functional group is first well designed for preparing advanced organosulfur polymer cathode without binder addition. This strategy not only solves the problem of low sulfur content in organosulfur polymer electrodes, but also solves the problem of uneven distribution of elemental sulfur in traditional carbon–sulfur composite electrodes under high sulfur content.